2019
DOI: 10.3389/fonc.2019.01292
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Long Non-coding RNAs in Immunotherapy Resistance

Abstract: T-cell-based immunotherapies, particularly immune checkpoint inhibitors, are promising treatments for various cancers. However, a large subset of patients develop primary or secondary resistance upon treatment. Although the detailed mechanisms remain unclear, immune escape via alterations in both cancer and tumor microenvironment has been identified as critical causes of immune resistance. Moreover, some long non-coding RNAs (lncRNAs), named as immune-related lncRNAs, have been recognized as regulators of immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 70 publications
0
42
0
Order By: Relevance
“…Akt, protein kinase B; lncRNA, long noncoding RNA; mTOR, mammalian target of rapamycin; NK, natural killer; PI3K, phosphatidylinositol-3-kinase F I G U R E 5 Association between the immune-related long noncoding RNA (lncRNA) signature and tumor immune cell infiltration. (a) Correlation between this signature and macrophages M0, (b) correlation between this signature and T cells follicular helper, (c) correlation between this signature and T cells regulatory (Tregs), (d) correlation between this signature and B cells memory, (e) correlation between this signature and eosinophils, (f) correlation between this signature and neutrophils, (g) correlation between this signature and dendritic cells activated, (h) correlation between this signature and T cells CD4 memory resting, (i) correlation between this signature and macrophages M1, (j) correlation between this signature and Mast cells resting, (k) correlation between this signature and B cells naive, (l) correlation between this signature and T cells gamma delta, (m) correlation between this signature and T cells CD8 biomarkers to provide potential support for clinic management and therapy in cancer (Heward & Lindsay, 2014;Xu et al, 2019;Y. Zhou, Zhu, Xie, & Ma, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Akt, protein kinase B; lncRNA, long noncoding RNA; mTOR, mammalian target of rapamycin; NK, natural killer; PI3K, phosphatidylinositol-3-kinase F I G U R E 5 Association between the immune-related long noncoding RNA (lncRNA) signature and tumor immune cell infiltration. (a) Correlation between this signature and macrophages M0, (b) correlation between this signature and T cells follicular helper, (c) correlation between this signature and T cells regulatory (Tregs), (d) correlation between this signature and B cells memory, (e) correlation between this signature and eosinophils, (f) correlation between this signature and neutrophils, (g) correlation between this signature and dendritic cells activated, (h) correlation between this signature and T cells CD4 memory resting, (i) correlation between this signature and macrophages M1, (j) correlation between this signature and Mast cells resting, (k) correlation between this signature and B cells naive, (l) correlation between this signature and T cells gamma delta, (m) correlation between this signature and T cells CD8 biomarkers to provide potential support for clinic management and therapy in cancer (Heward & Lindsay, 2014;Xu et al, 2019;Y. Zhou, Zhu, Xie, & Ma, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another research showed encouraging potentiality for new clinical management decisions on the basis of epigenetic regulation targeting LncMALAT1, which can coordinate with the immune system [37]. More and more evidences has strongly supported that immune-related lncRNAs may be novel disease biomolecules for cancer clinic treatment and possess valuable prognostic signi cance for survival [38,39]. Several immune-related lncRNA signatures have been explored in some tumors, such as bladder cancer, breast cancer, and colon cancer [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some immune-related lncRNAs regulate immunosuppressive mechanisms leading to immune evasion and resistance to immunotherapy. Some examples include loss of antigen presentation, PD-L1 overexpression, regulation of T-cell exhaustion, and MDSC and Treg differentiation and expansion (Zhou et al, 2019;Zheng et al, 2019).…”
Section: Tumor-extrinsic Factors and Resistance To Pd-l1/pd-1 Blockadmentioning
confidence: 99%